Sociodemographic, labor and clinical aspects of nursing professionals contaminated by COVID-19 (Research, Society and Development, 2021)
Objective: To describe the sociodemographic, clinical, and labor aspects of nursing professionals infected with COVID-19. Methodology: Cross-sectional descriptive study conducted with 237 nursing professionals in wo public hospitals in the Southwest region of Bahia, Brazil, who were infected with COVID-19, during the year 2020. Data collection took place in 2021, between January 5tth and February 4th, through a Google Forms questionnaire sent via a smartphone application. Variables were described by absolute and relative frequency, mean and standard deviation. Differences between professional categories were assessed using Pearson's chi-square test, linear trend test, or Fisher's exact test. Throughout the analysis, p values ​​0.05 were significant. Data were analyzed using the statistical package STATA version 15.0. Results: There was a predominance of females (90.7%), Afro-Brazilians (76.7%), with a mean age of 37.6 years, individual income ≤3,135. 00 (76.3%), salaried registered workers (62.8%), workers in critical areas (66.2%), workload ≤ 40 hrs. per week (70.8%), reported no comorbidity (73%) and no worsening of the clinical condition (64.5%). Conclusion: The sociodemographic and labor aspects of nursing professionals infected with COVID-19 corroborate the picture of this category in the rest of Brazil, revealing the social context and inequalities that permeate the working conditions and remuneration of these health workers.